Platelet Hyperactivation in Patients with Essential Thrombocythemia Is not Associated with Vascular Endothelial Cell Damage as Judged by the Level of Plasma Thrombomodulin, Protein S, PAI-1, t-PA and vWF - Bellucci, S; Ignatova, E; Jaillet, N; Boffa, M C (Thrombosis and Haemostasis, 1993)
The occurrence of thrombotic events remains an important clinical problem in Essential Thrombocythemias (ET). Thus, hemostatic, fibrinolytic and vascular status was investigated in 16 patients (5 males and 11 females) with ET. Among them five presented thromboses in their past history. Platelet hyperactivation, as evidenced by a mean three-fold increase in plasma betathromboglobulin (βTG), was observed in 13 among 16 patients; surprisingly this activation was present even when the platelet count was normal (in two patients) or subnormal, below 600 x 109/1 (in 11 patients). The mean value was 104 ± 57 IU/ml significantly different from that of normal controls (35 ± 16.5 IU/ ml) (p <0.001). An artefactual in vitro platelet activation was ruled out by the concomitant measurement of platelet factor, 4 (PF4). D-dimers fibrin degradation products (D-Di FDP) were normal in all patients. Vascular endothelial cell function parameters were not markedly modified. The mean value of plasma thrombomodulin ™ was found slightly but not significantly increased (60.1 ±4.9 ng/ml versus 49.1 ± 10.0 ng/ml in controls). The values of plasma TM correlated neither with that of the platelet count nor with that of plasma βTG or plasma PF4. The mean values of plasma protein S, von Willebrand factor (vWF), plasminogen activator inhibitor type 1 (PAI-1), tissue plasminogen activator (tPA) were normal and were not correlated neither with that of plasma TM nor with that of plasma βTG. In spite of a significant increase in vWF in two patients who presented peripheral thromboses, the markers of vascular endothelial cell function were not significantly different in patients having presented or not thromboses. Thus, in ET, these data showed the presence of platelet hyperactivation, even in patients in remission; it was not associated with vascular endothelial cell damage which might account for a greater risk of thrombosis.